If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6n + 2) = -238 Reorder the terms: 7(2 + 6n) = -238 (2 * 7 + 6n * 7) = -238 (14 + 42n) = -238 Solving 14 + 42n = -238 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 42n = -238 + -14 Combine like terms: 14 + -14 = 0 0 + 42n = -238 + -14 42n = -238 + -14 Combine like terms: -238 + -14 = -252 42n = -252 Divide each side by '42'. n = -6 Simplifying n = -6
| 5x-5+2x+97=180 | | (4+3i)(-2+5i)= | | p(14)=1+3(x+2)*(x+2) | | 8+18n+7n^2=0 | | 18-7n=4 | | 58=6x+4 | | 8+18n+7nsquared=0 | | 5x-5+x=180 | | (64x^4y^5)^1/4 | | 8+18n+7n*2=0 | | -14.2=-4.2g+6.9 | | 61=2x+3 | | 5p/pq | | 7x+35=56 | | 14-x-/2=x/5 | | 12n^2+2n+4=0 | | 2x^2-55x+150=0 | | 4x=486 | | 9m^2+52m-12= | | 7n^2+10=37n | | 5a^2=-6+11a | | 9x-(3x+2)=7x-17 | | 5x+12=162 | | 6n-1=-83 | | 3-2(1-8x)=4(6x+2)-7 | | 5x-2b=4 | | 7x+3b=23 | | x^2=342-x | | 5=5(x-2)-(x-7) | | 9x+9+11+11x=180 | | p-3(n-5)=30 | | 2-4-3x=3-4 |